Peran Motivasi Kerja Untuk Meningkatkan Produktivitas Karyawan di Toko H. Anwar Bantul dalam Perspektif Maqosyid Syariah - Rifa'i, Ahmad Sholahudin (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2024)
Based on observations, there are still some employees who are less professional at work, so work motivation is needed to increase employee productivity. This study aims to determine the factors that cause the need for work motivation to increase employee productivity, a form of realization of work motivation to increase employee productivity in the perspective of sharia maqasid. This study used descriptive qualitative. Data collection through interviews, observations and documentaries to obtain picture data from the object of research. The results of this study are categorized into 2 factors, namely internal factors in the form of meeting needs and increasing knowledge and skills as well as external factors in the form of relationships between superiors and subordinates and the work environment. As for the form of realization of work motivation, a person is encouraged to become more enthusiastic at work, income increases and employees become more productive. It is inseparable from the view of the sharia maqasid that employees have undergone a dharuriyah need in the form of maintaining religion, which is, employees have no compulsion regarding their beliefs. Maintaining the soul is that employees work to meet their needs. Maintain reason, namely employees’ always maintain their health by avoiding intoxicating drinks and drugs. Keeping offspring yes that employees prepare to marry by through work efforts. Safeguarding property is income obtained lawfully through trading.